STRATEGI PENGELOLAAN KEUANGAN USAHA KECIL DAN KEWIRAUSAHAAN KARANG TARUNA GEBANG KELURAHAN KADIPIRO KECAMATAN BANJARSARI SURAKARTA - Sumaryanto, Untung Sriwidodo & (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
Karang Taruna seen from the age factor is still young, they are still eager to move forward. No exception Karang Taruna Village Kampung Gebang Rt. 04 / Rw.17 Kaladahan Kadipiro. The problems that exist are the various socio-economic conditions, education, social status that exist in the members of Karang Taruna in Kampung Gebang, there are those who work, there are schools, lectures and many of them who have not worked even though they are actually ready to work Idle). The extension target is the members of youth group in Gebang village Rt.04 / Rw.17 Kadipiro Sub-District, Banjarsari District, Surakarta. The implementation method to overcome the problems of Karang Taruna in Kampung Gebang Rt.04 / Rw.17 Kalurahan Kadipiro, Banjarsari District Surakarta is to provide alternative solutions include: Counseling of small business management management system, extension of marketing and Entrepreneurship system, Counseling of financial management system. The results achieved from this community service program in Gebang Kalurahan Kadipiro are as follows: Increasing the motivation and ability of Karang Taruna in entrepreneurship, Improving the ability of Karang Taruna in managing the business, so it can develop well, Improving the ability of Karang Taruna in business management so that they will Know cash flow and can finally calculate the profit of his business, Improving the ability of Karang Taruna in terms of entrepreneurship, so they will be able to strategize and ultimately can be superior in choosing their business.Keywords: Marketing, Entrepreneurship, Financial management.